Physicians’ Behavior in Referring National Health Insurance Patients to Hospital - Natalia, Natalia (UI Scholars Hub, 2021)
Physicians’ decision to refer patients in primary health care is vital in supporting the referral system. The increase of referral cases impacted the claims cost and hospital workload. This study aimed to analyze the physicians’ behavior in referring National Health Insurance (NHI) patients to hospitals. This study employed a qualitative method; 18 informants were selected using purposive sampling and analyzed using content analysis. The data were validated by triangulating method, source, and data. Physicians referred patients when the cases could not be handled; there were indications of severe disease and required further examination. The obstacles in the referral system were pressure from NHI patients that wanted to be referred and diagnosed differently from ICD 10. In referring NHI patients, physicians had followed referral procedures and criteria. High referrals were caused by patients being forced to be referred, coming with complaints of severe disease, having examined in a hospital, and some cases should not be referred to but still referred by entering a similar diagnosis into the ICD 10. It is expected that public health centers will educate NHI patients related to tiered referral procedures in health services.